2006
DOI: 10.1038/sj.cdd.4401927
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into phagocytosis of apoptotic cells: proteolytic enzymes divert the recognition and clearance of polymorphonuclear leukocytes by macrophages

Abstract: The recognition of phosphatidylserine (PS) on the surface of any apoptotic cell is considered to be a key event for its clearance. We challenge this concept by showing that pretreatment of neutrophils with either host or bacterial protease affects their uptake by human monocyte-derived macrophages without having an effect on cell-surface PS presentation. Specifically, whereas preincubation of apoptotic neutrophils with cathepsin G or thrombin significantly inhibited their uptake, gingipains R or clostripain en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 49 publications
(51 reference statements)
1
48
0
Order By: Relevance
“…Nevertheless, plasmin's cleavage specificity is limited to lysine and arginine residues, and interestingly, gingipain R and clostripain, bacterial proteases with cleavage specificity after arginine, have been described to enhance apoptotic cell phagocytosis as well (18). Therefore, similar substrates might be cleaved by these proteases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, plasmin's cleavage specificity is limited to lysine and arginine residues, and interestingly, gingipain R and clostripain, bacterial proteases with cleavage specificity after arginine, have been described to enhance apoptotic cell phagocytosis as well (18). Therefore, similar substrates might be cleaved by these proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, similar substrates might be cleaved by these proteases. One such putative target was proposed to be the "don't-eat-me" signal CD31 (19), because CD31 surface staining declined after gingipain and clostripain treatment (18). Whether a "don't-eat-me" signal is indeed degraded or a novel "eat-me" signal is generated by the bacterial proteases and plasmin(ogen) remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several molecules or structures have been implicated as eat-me signals besides PS. These molecules include cell surface carbohydrates, oxidized lipids, intercellular adhesion molecule-3, cell surface calreticulin (for review, see Gardai et al, 2006), and certain unidentified molecules sensitive to proteolytic cleavage (Guzik et al, 2007). Lysophosphatidylcholine secreted from apoptotic cells was also reported to attract phagocytes to the vicinity (Lauber et al, 2003).…”
Section: The Evidence For a Novel Eat-me Signal(s)mentioning
confidence: 99%
“…streptopain, gingipains and ubiquitin-targeting proteases (Chiang-Ni & Wu, 2008;Edelmann & Kessler, 2008;Sheets et al, 2008). Gingipains R and a C. histolyticum homologue, Clo, have recently been shown to enhance the 'eat-me' signal of neutrophiles and induce their apoptosis (Guzik et al, 2007;Sheets et al, 2008;Guzik & Potempa, 2008). Clo and probably Clp seem likely to exert other pathogenic functions demonstrated for gingipains R. However, the involvement of these clostridial proteases in myonecrosis has remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is secreted as an inactive precursor form, which is converted to a heterodimeric active form through autocatalytic removal of a propeptide and a linker peptide (Dargatz et al, 1993;Ullmann & Bordusa, 2004). Recently, it was shown that Clo facilitates the apoptosis of neutrophiles, as do gingipains R, the major virulence factors of periodontopathogenic Porphyromonas gingivalis (Guzik et al, 2007;Sheets et al, 2008;Guzik & Potempa, 2008). Other pathogenic functions implicated for gingipains R seem also to be exerted by Clo, since these arginine-specific endopeptidases are closely related to each other both phylogenetically and structurally (Chen et al, 1998;Barrett & Rawlings, 2001;Labrou & Rigden, 2004).…”
Section: Introductionmentioning
confidence: 99%